Back to Black: Values, Ideology and the Black Box of Political Radicalization - Capelos, Tereza; Katsanidou, Alexia; Demertzis, Nicolas (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2017)
This article focuses on the psychological drivers of anomic and violent behaviors described as ‘new radicalisms’ in the context of the Eurozone economic crisis. The authors make a conceptual and empirical distinction between the desire for change forward against the old (defined as radicalism) and the desire for change backward against the new (defined as reactionism). Using 2015 data from Greece, multinomial logit models test the role of core values that map on the desire for change against the new and the desire for change against the old as predictors of dormant and actualized anomic and violent behaviors. The findings support that desire for conservation triggered reactionist political engagement in Greece that spans across the left/right ideology spectrum.